The project as a tool for solving the problems of territorial communities affected by military actions - Spirina Tеtiana; Martyniuk Yana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
The challenges currently faced by territorial communities are also an opportunity to establish social partnership and lay the foundation for qualitative transformations. In particular, project activity, thanks to purposefulness, orientation to the result, will contribute to the efficiency and quality of life of residents of territorial communities, strengthening their resource and competitive potential. The ongoing war requires the search for modern mechanisms for solving social, socio-cultural, economic, political, societal problems and ensuring the urgent needs of territorial communities affected by military actions. In the article, the authors note certain characterological features of territorial communities: economic; historical and cultural; organizational and functional; political; natural; socio-psychological; territorial. A thorough and detailed assessment by communities of their own needs will serve to implement innovative forms of citizen involvement in local self-government. The community’s determination and assessment of its own needs involves the following stages: organization of assessment groups; definition of the goal; support of a meaningful environment; assessment planning; assessment; formation of working groups; informing the community about the assessment results. Namely, communities’ assessment of their own needs is an important factor in making responsible, effective management decisions regarding the successful development of territorial communities affected by military actions. Involvement of social workers, social work specialists, volunteers, residents of territorial communities in assessing their own problems and needs contributes not only to social cohesion, but also causes effective territorial development of the community.